Applied photovoltaics - Wenham, S. R. (Earthscan, 2007)
This textbook features a set of detailed technical appendices that provide essential equations, data sources, and standards. It provides the reader with all the information needed to work with photovoltaics.
Keywords: Photovoltaic power generation.; Photovoltaic cells.; elektronické knihy; electronic books